Overview of integrated animals-crops-fish production systems: Achievements and future potential - Devendra, C. (Japanese Society of Zootechnical Science, 1996)
An overview of integrated animals-crops-fish production systems is discussed with reference to the relevance, achievements and future potential of these systems. The relevance of these systems is reflected in the nature of traditional mixed farming systems in Asia, from where over 90 percent of the meat and milk is produced in these situations. Two broad categories of integrated systems are identified: systems combining animals and annual cropping, and systems combining animals and perennial cropping. The positive environmental and economic impacts that result from the interactions of the individual components (animals, crops, land and water) are enumerated. Major achievements in respect of each of these systems are highlighted and also the impact of integrated crop-animal systems in 10 long term case studies. The need for further research and Development direction in the future is emphasised with reference to key aspects within the effects of primary crop management on animals, and effects of animal integration on the parent crop, economic analysis, sustainability, institutional issues, and policy support. The expansion and intensification of integrated systems is also associated with the concurrent intensive use of available agro-industrial by-products in situ as in the case of oil palm. The future for developing largescale integrated systems is linked with the need to extend research and Development to the rainfed lowland and upland areas, where also is found large concentrations of cattle, goats and sheep. The potential benefits are directly associated with a more concerted role for animals, increased productivity from these zones, and demonstration of environmentally sustainable integrated production systems.